PENERAPAN TEKNOLOGI BUDIDAYA TANAMAN AREN DENGAN BEBERAPA PUPUK ORGANIK UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI NAGARI SUNGAI DAREH KABUPATEN DHARMASRAYA - Suhendra, Dede; Dwipa, Indra; Yanti, Yulmira; Rezki, Dewi; Karjunita, Nike; Lubis, Reynaldi Fasya Abdullah; Tajudin, Rian (Jurnal Abdi Insani, 2025)
Sugar palm is a plant that has high economic potential, but its cultivation in Indonesia is still lacking in attention. The demand for palm sugar will continue to increase, so it is important to develop the cultivation of this plant with environmentally friendly methods. Through the Community Partnership Helping Businesses Grow (PKM MUB) program, a community service team consisting of academics and students from Andalas University collaborated with the Bukik Kandang Forest Farmers Group. Identification of problems includes slow growth of sugar palm plants due to lack of proper maintenance and fertilization. Therefore, this community service proposes the use of organic fertilizers, such as buffalo manure, palm oil mill liquid waste, and solid decanters, to increase plant growth. The methods used include socialization, training, and assistance to farmers in implementing efficient cultivation technology by observing all activities in the field that include aspects of sugar palm cultivation. The stages carried out in this activity include: Location survey, demonstration socialization, land clearing, preparation of organic materials, application of organic fertilizers, preparation of seeds, planting, and maintenance. The target output of this community service is an accredited scientific article and increased productivity and farmer welfare. These expected steps can improve food security and contribute to local economic development as well as environmental preservation and the application of sugar palm cultivation technology by utilizing several types of organic fertilizers, which have been proven to improve plant growth and farmer welfare in Nagari Sungai Dareh. Through socialization, training, and mentoring methods, farmers gain a better understanding of environmentally friendly plant maintenance techniques.